PROBLEMS AND PROSPECTS OF DEVELOPMENT OF SECURITIES MARKET: DOMESTIC AND INTERNATIONAL EXPERIENCE (International relations and international law Journal, 2016)
For today, the securities market is one of the most important areas of the economy. The securities market facilitates and enhances access to all economic entities to obtain the necessary ﬁnancial resources to them. Without a functioning securities market can not be a real economic recovery. In general, based on macroeconomic forecasts, we are optimistic about the global equity markets. And the Kazakhstan market can not be an exception.
Keywords: securities; Kazakhstan Stock Exchange